2021
DOI: 10.1096/fj.202101276r
|View full text |Cite
|
Sign up to set email alerts
|

Maternal fructose intake predisposes rat offspring to metabolic disorders via abnormal hepatic programming

Abstract: Given that fructose consumption has increased by more than 10‐fold in recent decades, it is possible that excess maternal fructose consumption causes harmful effects in the next generation. This study attempted to elucidate the mechanism of the harmful effects of excessive maternal fructose intake from the perspective of offspring liver function. Female rats during gestation and lactation were fed water containing fructose, and their offspring were fed normal water. We attempted to elucidate the mechanism of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…1.00 ± 0.09 1.20 ± 0.12* 1.00 ± 0.14 may be because of differences in the concentration of fructose administration and length of the intake period. According to our previous studies, exposure to fructose during early life stages such as fetal and lactation induces changes in miRNA expression and DNA methylation level in the liver [23,40]. These epigenetic modifications may be maintained at least until adulthood, altering mRNA expression of genes related to lipid metabolism.…”
Section: Liver Hsd11b1mentioning
confidence: 91%
“…1.00 ± 0.09 1.20 ± 0.12* 1.00 ± 0.14 may be because of differences in the concentration of fructose administration and length of the intake period. According to our previous studies, exposure to fructose during early life stages such as fetal and lactation induces changes in miRNA expression and DNA methylation level in the liver [23,40]. These epigenetic modifications may be maintained at least until adulthood, altering mRNA expression of genes related to lipid metabolism.…”
Section: Liver Hsd11b1mentioning
confidence: 91%
“…Consistent with a previous study, Munetsuna et al found that maternal fructose intake resulted in an increase in miR-29a in the livers of the offspring at 160 days of age, which decreased Igf1 mRNA expression. Moreover, reduced IGF1 expression may induce IR and impair hepatic function ( 125 ). However, no impaired IR or decreased high-density lipoprotein cholesterol (HDL-C) levels were observed at 60 days of age, even with the increase in miR-29a ( 125 ).…”
Section: Role Of Mirnas In Both Glucose and Lipid Metabolism In Offsp...mentioning
confidence: 99%
“…Moreover, reduced IGF1 expression may induce IR and impair hepatic function ( 125 ). However, no impaired IR or decreased high-density lipoprotein cholesterol (HDL-C) levels were observed at 60 days of age, even with the increase in miR-29a ( 125 ). Therefore, it is possible to use the expression of miRNAs to predict the metabolic state later in life.…”
Section: Role Of Mirnas In Both Glucose and Lipid Metabolism In Offsp...mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common types of epigenetic modifications are DNA methylation and the effects of microRNAs (miRNAs), which can either activate or repress gene expression [19]. We previously reported that excess maternal fructose causes epigenetic abnormalities in offspring [20,21], which may explain the increase in circulating GC levels.…”
Section: Introductionmentioning
confidence: 99%